Feasibility of Digital Comic Media in Enhancing Early Reading Skills for First-Grade Elementary School Students - Vadila Nurista Ananda; Kadek Yudiana; Putu Rahayu Ujianti (Jurnal Edutech Undiksha, 2024)
Not all new students are able to understand letters or reading materials effectively. Many first-grade elementary school students still face challenges in learning to read. This study aims to develop a digital comic learning media designed to improve the reading skills of first-grade elementary school students, particularly on the topic of "Forgiveness." The research type is developmental research using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects included material experts, media experts, and educational practitioners. The trial subjects consisted of first-grade students, involving an individual trial with three students and a small group trial with nine students. Data collection methods utilized a rating scale with a questionnaire as the instrument. The data analysis technique employed both quantitative and qualitative descriptive analysis. The results of the study showed that the evaluation of the material and media tests using Aiken's V formula yielded a percentage of 98%, categorized as "very good." Additionally, the practitioner test analysis indicated a 100% percentage with a "very good" qualification. The individual trial results showed a 100% score, categorized as "very practical." Based on these findings, it can be concluded that digital comic learning media is feasible to be used in learning to enhance the reading skills of first-grade elementary school students.